UJI EFEKTIVITAS CAIRAN ECO ENZYME SEBAGAI DISINFEKTAN DALAM MENURUNKAN ANGKA KUMAN PADA LANTAI DI RUANG RAWAT INAP RUMAH SAKIT RATU ZALECHA MARTAPURA - Sawitri, Deswita Dwi; Rahmawati, Rahmawati; Erminawati, Erminawati (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Hospital is currently still using chemical disinfectants as floor cleaners. Most chemical disinfectants contain ingredients that are harmful to human health and the environment. An alternative solution to replace chemical floor cleaners by using natural-based floor cleaners, one of which is eco-enzyme. The aim of the research was to determine the effectiveness of administering eco-enzyme fluid in reducing the number of floor germs in one of the inpatient rooms at Ratu Zalecha Martapura Hospital. This research was true experimental in nature, carried out with trials using 3 variations of concentration, namely 1%, 3% and 6%, with 6 repetitions and a total of 24 samples. Examination of floor germ numbers is carried out at the District Health Laboratory. Banjar. Differences in germ numbers in floor swab samples were analyzed using the One way Anova test. The results of the One way Anova statistical test showed that there was a significant difference between the number of floor germs before and after eco-enzyme treatment with concentrations of 1%, 3%, 6%. The average number of germs on the floor of the Merpati 5 class 2 inpatient room before eco-enzyme treatment was 14 cfu/cm². After eco-enzyme treatment with concentrations of 1%, 3%, 6% the average germ number decreased to 6, 3, 1 cfu/cm². So it can be concluded that the greater the concentration of eco-enzyme,the greater its ability to reduce the number of floor germs. It is hoped that the hospital can use eco-enzyme liquid with a concentration of 6% as a natural disinfectant. In order to use eco-enzyme fluid more effectively, you can pay attention to the cleanliness of the floor. By reducing the number of visitors and the number of patients waiting to enter the treatment room.